The Revolution of The Qur’anic Interpretation (Criticism of The Jamal Al-Banna’s Methodology in 1920 - 2013) - Abdul Mufid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
The study of interpretation methodology is very important, because the activities of the interpretation of the Koran will continue to develop along with the pace of the times. Abdul Mustaqim has mapped the interpretation methodology into three parts. First, the interpretation of the classical period. Second, the interpretation of the middle period. Third, interpretation of the contemporary period. With this mapping, it is expected that the position of the interpretation methodology of Jamal al-Banna can be known making it easier for researchers to recognize the interpretive concepts they offer. In every generation there are always products of interpretation of the Koran that have different features and characteristics. The socio-cultural condition in which the interpreter lives and the background of the disciplines they pursue is a reality that influences their interpretation of the Qur'an. The emergence of contemporary interpretations as the development of a scientific discipline is also much influenced by the development and change of the scientific epistemology itself. In this contemporary era, the name Jamal al-Banna appears which offers a new methodology for interpretation. This Egyptian-born thinker criticizes the scientific tradition of interpretation that has developed over the years (both classical and contemporary). So do not be surprised if the various ideas are always controversial. This article tries to review the methodological and philosophical interpretation of Jamal al - Banna. Starting with the effort to deconstruct the interpretation of the results of all classical commentators, Jamal proposed three stages in the interpretation of the Koran, namely the art approach, psychological approach, and rational approach. All three are hierarchical stages to arrive at an interpretation. Having arrived at the interpretation stage, Jamal al- Banna does not recommend certain methods or limit certain knowledge as methods of interpretation analysis. He refused if one particular method has a guarantee as the only way to find the truth, because the Koran does not have to be limited. Some contemporary thinkers in the study of the Koran, such as Amin al-Khuli, Mohammed Syahrur, Mohammed Arkoun, Nashr Hamid Abu Zayd, and Orientalist views on the Koran also did not escape criticism. To find out more about Jamal's thought, this article uses a descriptive qualitative method and a philosophical-rationalistic approach with hermeneutics as the ISSN: 1411-1632 (Print) 2527-5992 (Online) knife of analysis. Both of these methodologies are used to reveal the construct of Jamal's thought around the interpretation methodology that he built. This study contributes positively in order to broaden the insight of the study around the conceptual interpretation of the Koran. Because the spirit and problems faced by muslims today are growing and complex which demands the discovery of new methods in understanding the Koran more accommodatively and dynamically. Based on the method and approach above, it was found that the interpretation method conceived by Jamal wanted to place the Koran free of the various approaches that limit it. For Jamal, humans are very autonomous and free to interpret as long as it is in line with the humanist and universal principles contained in the Koran. Through the systematic-practical interpretation methodology offered above, it can facilitate the moslem community to comprehend the Koran comprehensively. The study of interpretation methodology is very important, because the activities of the interpretation of the Koran will continue to develop along with the pace of the times. Abdul Mustaqim has mapped the interpretation methodology into three parts. First, the interpretation of the classical period. Second, the interpretation of the middle period. Third, interpretation of the contemporary period. With this mapping, it is expected that the position of the interpretation methodology of Jamal al-Banna can be known making it easier for researchers to recognize the interpretive concepts they offer. In every generation there are always products of interpretation of the Koran that have different features and characteristics. The socio-cultural condition in which the interpreter lives and the background of the disciplines they pursue is a reality that influences their interpretation of the Qur'an. The emergence of contemporary interpretations as the development of a scientific discipline is also much influenced by the development and change of the scientific epistemology itself. In this contemporary era, the name Jamal al-Banna appears which offers a new methodology for interpretation. This Egyptian-born thinker criticizes the scientific tradition of interpretation that has developed over the years (both classical and contemporary). So do not be surprised if the various ideas are always controversial. This article tries to review the methodological and philosophical interpretation of Jamal al - Banna. Starting with the effort to deconstruct the interpretation of the results of all classical commentators, Jamal proposed three stages in the interpretation of the Koran, namely the art approach, psychological approach, and rational approach. All three are hierarchical stages to arrive at an interpretation. Having arrived at the interpretation stage, Jamal al- Banna does not recommend certain methods or limit certain knowledge as methods of interpretation analysis. He refused if one particular method has a guarantee as the only way to find the truth, because the Koran does not have to be limited. Some contemporary thinkers in the study of the Koran, such as Amin al-Khuli, Mohammed Syahrur, Mohammed Arkoun, Nashr Hamid Abu Zayd, and Orientalist views on the Koran also did not escape criticism. To find out more about Jamal's thought, this article uses a descriptive qualitative method and a philosophical-rationalistic approach with hermeneutics as the knife of analysis. Both of these methodologies are used to reveal the construct of Jamal's thought around the interpretation methodology that he built. This study contributes positively in order to broaden the insight of the study around the conceptual interpretation of the Koran. Because the spirit and problems faced by muslims today are growing and complex which demands the discovery of new methods in understanding the Koran more accommodatively and dynamically. Based on the method and approach above, it was found that the interpretation method conceived by Jamal wanted to place the Koran free of the various approaches that limit it. For Jamal, humans are very autonomous and free to interpret as long as it is in line with the humanist and universal principles contained in the Koran. Through the systematic-practical interpretation methodology offered above, it can facilitate the moslem community to comprehend the Koran comprehensively.